Understanding the emergence and trajectory of job insecurity due to smart technology, artificial intelligence, robotics, and automation - Walczok, Marvin; Bipp, Tanja (Human factors and ergonomics in manufacturing & service industries, 2025)
Smart technologies, artificial intelligence, robotics, and automation (STARA) can revolutionize the labor market by substituting human labor. STARA Awareness has been introduced to capture employees' appraisal of the impact of STARA on their employment without a thorough validation and overarching theoretical framework. Therefore, we contributed a content validation of STARA Awareness and examined the internal structure of the suggested measurement instrument, the differentiation from cognitive and affective job insecurity (JI), potential antecedents, and its 1-year trend. We conducted two cross-sectional (N1 = 215, N2 = 224) and one longitudinal study (N3 = 233) with German employees from various branches. We adapted the questionnaire and redefined the construct as affective automation-related job insecurity (AAJI) based on content criticism. Our results indicate that AAJI is weakly positively related to cognitive and affective JI but empirically different. We identified the substitution potential of occupation, the use of STARA as positive predictors, and core self-evaluations as a negative predictor of AAJI. Latent growth curve models reveal no linear change of AAJI over 1 year but different trajectories as a function of the use of STARA. Thus, AAJI represents a digitalization-specific form of job insecurity with its distinct nomological net and high temporal stability.